PEMANTAUAN KEKERUHAN DAN NILAI TOTAL DISSOLVED SOLIDS KUALITAS AIR AKUARIUM MENGGUNAKAN METODE FUZZY LOGIC MAMDANI - Nur Zahra Lutfia (JURNAL TELISKA, 2025)
The quality of aquarium water is crucial for the health of fish and other organisms. Turbidity and Total Dissolved Solids (TDS) are two main factors affecting water quality. This study aims to develop an automatic system to control aquarium water quality using the Mamdani Fuzzy Logic method. This method was chosen for its ability to handle uncertain or incomplete data. We defined fuzzy membership functions for turbidity (clear, murky, very murky) and TDS (low, medium, high), and created rules to control the pump status (On/Off). Using the centroid defuzzification method, the system provides clear decisions for regulating the pump. The results show that this system is effective in controlling the aquarium pump based on turbidity and TDS, thus improving water quality and reducing sudden changes in these parameters. Tuliskan abstrak Anda dalam bahasa Inggris (Maksimal 200 kata, font Times New Roman ukuran 10, rata kiri kanan/Justify)